Algorithmization of the World of Life: Criticism and Proposals for the De-differentiation - Urban, Bárbara (Revista del CLAD Reforma y Democracia, 2020)
Jürgen Habermas speaks about technocracy referring to the dissociation of the whole formed by the society’s self-understanding from the system of reference, the communicative action and the symbolic interaction. As a result, we find a politicized usage of technological elements, such as algorithms, which have even served to influence democratic electoral processes. The solution to this fact must involve a practical use of communicative action, to boost commitment, thus adopting a deliberative democratic model in which companies participate as producers of science and technology.
Keywords: Democracy; State-Society Relationship; Technocracy; Science and Technology; Quality of Life